HUBUNGAN DUKUNGAN KELUARGA DENGAN PELAKSANAAN PERILAKU CERDIK PADA PASIEN DIABETES MELITUS TIPE 2 - Rahayu Saputri, Jihan; Saputra, Bayu; Abdur Rasyid, Tengku (JURNAL KESEHATAN KARTIKA, 2025)
Background: Diabetes mellitus is directly related to lifestyle, management is needed by implementing healthy habits through CERDIK behavior with the help of family support. Objective: To identify the relationship between family support and the implementation of CERDIK behavior in patients with type 2 diabetes mellitus. Methods: This type of research is quantitative with a correlational design and uses a crossectional approach with a total sample of 70 people taken using consecutive sampling technique with the criteria of respondents aged more than 18 years, patients who visit for treatment and health control at the internal medicine clinic of Arifin Achmad Hospital, Riau Province. Data were collected using 12 questions of family support questionnaire, and 6 questions of CERDIK behavior questionnaire that have been tested for validity and reliability. The analysis used was univariate analysis and bivariate analysis. Results: The majority of women were 67.1%, with an average age of 53.57 years, 37.1% had a high school education, 88.6% were married, 81.4% were diagnosed with type 2 diabetes mellitus for > 6 months, and 54.3% were cared for by a spouse. CERDIK behavior was implemented by 70% while 30% were not implemented, and good and sufficient family support was 77.1%. Fisher's test with p value = 0.004. Conclusion: There is a relationship between family support and the implementation of CERDIK behavior in patients with type 2 diabetes mellitus at RSUD Arifin Achmad Riau. Effective interventions are expected to improve family support for diabetes patients.